Antibody Fc engineering improves frequency and promotes kinetic boosting of serial killing mediated by NK cells - Romain, Gabrielle (Blood, 2014)
The efficacy of most therapeutic monoclonal antibodies (mAbs) targeting tumor antigens results primarily from their ability to elicit potent cytotoxicity through effector-mediated functions. We have engineered the fragment crystallizable (Fc) region of the immunoglobulin G (IgG) mAb, HuM195, targeting the leukemic antigen CD33, by introducing the triple mutation Ser293Asp/Ala330Leu/Ile332Glu (DLE), and developed Time-lapse Imaging Microscopy in Nanowell Grids to analyze antibody-dependent cell-mediated cytotoxicity kinetics of thousands of individual natural killer (NK) cells and mAb-coated target cells. We demonstrate that the DLE-HuM195 antibody increases both the quality and the quantity of NK cell-mediated antibody-dependent cytotoxicity by endowing more NK cells to participate in cytotoxicity via accrued CD16-mediated signaling and by increasing serial killing of target cells. NK cells encountering targets coated with DLE-HuM195 induce rapid target cell apoptosis by promoting simultaneous conjugates to multiple target cells and induce apoptosis in twice the number of target cells within the same period as the wild-type mAb. Enhanced target killing was also associated with increased frequency of NK cells undergoing apoptosis, but this effect was donor-dependent. Antibody-based therapies targeting tumor antigens will benefit from a better understanding of cell-mediated tumor elimination, and our work opens further opportunities for the therapeutic targeting of CD33 in the treatment of acute myeloid leukemia.